Survival characteristics and transcriptome profiling reveal the adaptive response of the Brucella melitensis 16M biofilm to osmotic stress - Guo, Jia; Zhu, Jiale; Zhao, Tianyi; Sun, Zhihua; Song, Shengnan; Zhang, Yu; Zhu, Dexin; Cao, Shuzhu; Deng, Xingmei; Chai, Yingjin; Sun, Yongxue; Maratbek, Suleimenov; et al. (Frontiers in Microbiology, 2022)
Brucella can inhabit hostile environments, including osmotic stress. How Brucella responds collectively to osmotic stress is largely unexplored, particularly in spatially structured communities such as a biofilm. To gain insight into this growth mode, we set out to characterize the Brucella melitensis 16M biofilm, describe its phenotype, and carry out a comparative transcriptomic analysis between biofilms under osmotic stress and control conditions. We determined that the bacteria challenged with 1.5 M NaCl had a reduced ability to aggregate and form clumps and develop a biofilm; however, the salt stress promoted the release of the outer membrane vesicles from the biofilm. Together with the genotypical response to osmotic stress, we identified 279 differentially expressed genes in B. melitensis 16M grown under osmotic conditions compared with control conditions; 69 genes were upregulated and 210 downregulated. Under osmotic stress, the main changed genes of biofilm were predicted to be involved in flagellar assembly, cell envelope, translation, small RNA regulation, transport and binding proteins, and energy metabolism. In addition, the ABC transporter was enriched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. We highlight 12 essential ABC transporter genes associated with a bacterial response to osmotic stress at the biofilm stage, including one specific locus, BME_RS12880, mediating betaine accumulation in biofilms to eliminate osmotic stress. The current study results can help researchers gain insights into B. melitensis 16M biofilm adaptation to osmotic stress and provide information for developing intervention strategies to control Brucella.